Mental illness in primary care: a narrative review of patient, GP and population factors that affect prescribing rates. (2nd March 2020) - Tobin, H.; Bury, G.; Cullen, W.
Abstract : Background: Mental illness poses a large and growing disease burden worldwide. Its management is increasingly provided by primary care. The prescribing of psychotropic drugs in general practice has risen in recent decades, and variation in prescribing rates has been identified by a number of studies. It is unclear which factors lead to this variation. Aim: To describe the variables that cause variation in prescribing rates for psychotropic drugs between general practices. Methods: A narrative review was conducted in January 2018 by searching electronic databases using the PRISMA statement. Studies investigating causal factors for variation in psychotropic prescribing between at least two general practice sites were eligible for inclusion. Results: Ten studies met the inclusion criteria. Prescribing rates varied considerably between practices. Positive associations were found for many variables, including social deprivation, ethnicity, patient age and gender, urban location, co-morbidities, chronic diseases and GP demographics. However studies show conflicting findings, and no single regression model explained more than 57% of the variation in prescribing rates. Discussion: There is no consensus on the factors that most predict prescribing rates. Most research was conducted in countries with central electronic databases, such as the United Kingdom; it is unclear whether these findings apply in other healthcare systems. More research is needed to determine the variables that explain prescribing rates for psychotropic medications.